The potential and importance of exercise therapy in pediatric oncology - The PrepAIR study - Fiona Streckmann; Christina Schindera; Oliver Faude; Nicolas von der Weid (Bern Open Publishing, 2024)
Introduction Modern therapy has improved survival for children with cancer. However, treatment takes its toll. Children experience delays in motor development milestones such as walking, running, jumping or climbing, diminishing children's quality of life and affecting their social reintegration. One side-effect of chemotherapy and crucial cause of the many dysfunctions is a peripheral neuropathy (CIPN). Depending on the neurotoxic agent, 52%-100% of children are affected (Kandula et al. 2016). It causes severe symptoms such as loss of sensation, numbness, pain, absent reflexes as well as loss of balance control. It is also of high clinical relevance as it affects medical therapy. Additionally, recovery is poor and there are currently no treatment options (Loprinzi et al. 2020). Previous research has shown (Streckmann et al. 2022) promising results: Specific exercises can reduce symptoms of CIPN and improve patients' quality of life. In our most recent study in adults, we were also able to prevent the onset of CIPN with clinical impact. We hypothesize that CIPN could be the root of many problems children experience during therapy. Our aim is to maintain relevant sensory and motor functions in children in order for them to receive their planned medical therapy and become fitter and socially better integrated survivors. Methods We are therefore currently running a large, prospective, multicenter, randomized controlled trial (Basel, Bern, Aarau, St. Gallen, Freiburg (D) and Berlin (D)), randomizing N = 131 children planned to receive a neurotoxic chemotherapy into an intervention group or a treatment as usual group and accompanying them throughout their oncological therapy. After therapy the control group will also be shown the training. Primary endpoint is the incidence of CIPN, secondary endpoints are postural control, dorsiflexion function, knee extension strength, lower limb power, walk to run transition time, CIPN-related pain, participation of exercise-related leisure activities, children's' physical self-concept and quality of life. Discussion/Conclusion We hypothesize that less children in the intervention group will develop symptoms of CIPN and will be able to maintain relevant motor and sensory functions which will enable them to receive their planned medical therapy but also to stay on the age-appropriate motor development level, improve their quality life and enhance social reintegration after therapy. This would show that specific exercise therapy is more than just a lifestyle intervention, it could be a therapy option without further side- effects, changing supportive care in oncology. This study will therefore contribute to our endeavors to implement exercise therapy in pediatric oncology long-term empowering patients to return to an active lifestyle and additionally reduce the risk of long-term secondary diseases. References Kandula, T., Park, S. B., Cohn, R. J., Krishnan, A. V., & Farrar, M. A (2016). Pediatric chemotherapy induced peripheral neuropathy: A systematic review of current knowledge. Cancer Treatment Reviews, 50, 118-128. https://doi.org/10.1016/j.ctrv.2016.09.005 Loprinzi, C. L., Lacchetti, C., Bleeker, J., Cavaletti, G., Chauhan, C., Hertz, D. L., Kelley, M. R., Lavino, A., Lustberg, M. B., Paice, J. A., Schneider, B. P., Lavoie Smith, E. M., Smith, M. L., Smith, T. J., Wagner-Johnston, N., & Hershman, D. L. (2020). Prevention and management of chemotherapy-induced peripheral neuropathy in survivors of adult cancers: ASCO guideline update. Journal of Clinical Oncology, 38(28), 3325-3348. https://doi.org/10.1200/jco.20.01399 Streckmann, F., Balke, M., Cavaletti, G., Toscanelli, A., Bloch, W., Décard, B. F., Lehmann, H. C., & Faude, O. (2022). Exercise and neuropathy: Systematic review with meta-analysis. Sports Medicine, 52(5), 1043-1065. https://doi.org/10.1007/s40279-021-01596-6